Geotechnical sustainability in the United Arab Emirates - Sustainability rating tools - Sochanik, Ryan (International Journal of Engineering and Technology, 2020)
Sustainability and the concept of sustainable development now forms part of governmental policy around the world. The United Arab Emirates is no different, recognising that its ecological footprint and continued growth require management of resources and waste streams. A fundamental part of this is sustainable construction and operation of civil engineering projects such as buildings, roads and airports. Geotechnical engineering is required on practically all civil engineering projects yet is often overlooked when design and construction decisions are being made regarding civil engineering sustainability. One of the most common ways to measure sustainability in civil engineering projects is through rating tools. Rating tools have grown and developed internationally for decades and are used across the world for various different projects (buildings, roads, infrastructure etc.). The United Arab Emirates have developed their own local ratings tools (and sustainability frameworks) and have mandated their use in certain projects. There is significant scope for geotechnical engineering to contribute to improving sustainability and rating tools are one element that can be developed. A detailed review of local and international ratings tools is carried out to understand where geotechnical engineering can currently contribute and the possibilities to improve geotechnical sustainability in the United Arab Emirates are discussed.Â Â